Endothelial autophagy deficiency induces IL6 - dependent endothelial mesenchymal transition and organ fibrosis. Issue 10 (2nd October 2020) - Takagaki, Yuta; Lee, Seon Myeong; Dongqing, Zha; Kitada, Munehiro; Kanasaki, Keizo; Koya, Daisuke
ABSTRACT: Macroautophagy/autophagy plays a vital role in the homeostasis of diverse cell types. Vascular endothelial cells contribute to vascular health and play a unique role in vascular biology. Here, we demonstrated that autophagy defects in endothelial cells induced IL6 (interleukin 6)-dependent endothelial-to-mesenchymal transition (EndMT) and organ fibrosis with metabolic defects in mice. Inhibition of autophagy, either by a specific inhibitor or small interfering RNA (siRNA) for ATG5 (autophagy related 5), in human microvascular endothelial cells (HMVECs) induced EndMT. The IL6 level was significantly higher in ATG5 siRNA-transfected HMVECs culture medium compared with the control HMVECs culture medium, and neutralization of IL6 by a specific antibody completely inhibited EndMT in ATG5 siRNA-transfected HMVECs. Similar to the in vitro data, endothelial-specific atg5 knockout mice (Atg5 Endo; Cdh5-Cre Atg5 flox/flox mice) displayed both EndMT-associated kidney and heart fibrosis when compared to littermate controls. The plasma level of IL6 was higher in Atg5 Endo compared to that of control mice, and fibrosis was accelerated in Atg5 Endo treated with a HFD; neutralization of IL6 by a specific antibody inhibited EndMT and fibrosis in HFD-fed Atg5 Endo associated with the amelioration of metabolic defects. These results revealed the essential role of autophagy in endothelial cell integrity and revealed that the disruption of endothelial autophagy could lead to significant pathological IL6-dependent EndMT and organ fibrosis. Abbreviations : 3-MA: 3-methyladenine; ATG5: autophagy related 5; EndMT: endothelial-to-mesenchymal transition; HES: hematoxylin and eosin stain; HFD: high-fat diet; HMVECs: human microvascular endothelial cells; IFNG: interferon gamma; IL6: interleukin 6; MTS: Masson's trichrome staining; NFD: normal-fat diet; siRNA: small interfering RNA; SMAD3: SMAD family member 3; TGFB: transforming growth factor β; TNF: tumor necrosis factor; VEGFA: vascular endothelial growth factor A